Anti-Bacterial Activity Testing Of Batak (Allium Chinense G. Don.) Leaf Ethanol Extract Against The Bacteria Propionibacterium Acnes, Staphylococcus Aureus, Escherichia Coli And Salmonella Thyph - Nina Irmayanti Harahap; Rika Puspita sari; Zola Efa Harnis; Sri Rezeky (Institute Of Computer Science (IOCS), 2022)
Batak onion (Allium chinense G.Don) of the Amarylidaceae family is one of the traditional medicinal plants that has antibacterial properties, containing flavonoids, terpenoids, tannins and saponins. EEDBB extract against Propionibacterium acne (Pa), Staphylococcus aureus (Sa), Eschericia coli (Ec), Salmonella typhi (St). Batak shallot powder was extracted by maceration method using 80% ethanol as solvent. disc diffusion method of advertising concentration (EEDBB) 40%, 60%, 80% with a comparison of positive control and negative control. Measurement of antibacterial activity showed that all concentrations had antibacterial activity. The highest antibacterial activity of EEDBB at a concentration of 80% had a maximum antibacterial with an average inhibition zone of 11.5 mm for bacteria (Pa), 10 mm for bacteria (Sa), 15,5 mm for bacteria (Ec) and 16.1 mm for bacteria. bacteria (St). The lowest antibacterial activity ethanol extract at a concentration of 40% had the lowest inhibitory power with an average inhibition zone diameter of 7.8 mm for bacteria (Pa), 6.6 mm for bacteria (Sa), 12.9 mm for bacteria (Pa). . bacteria (Ec) and 13.2 mm in bacteria (St). EEDBB has the highest antibacterial activity on bacteria (St) with an average inhibition zone of 16mm. Data analysis was carried out using the One way ANOVA test, namely H0 was accepted and H1 was rejected where the value of sig < 0.05.